Improving Speaking Proficiency Via Role-Play: An Investigation From Indonesian Secondary Schools - Renanda, Cintassa Agni; Yunus, Muhammad; Rachmawati , Siti (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2025)
Speaking remains one of the most challenging skills for EFL students in Indonesia. Many students face anxiety and lack of opportunities to practice speaking English in authentic contexts. This Classroom Action Research was carried out to develop the speaking abilities of 6B2 students at SMP Negeri 5 Malang by applying the role-play method. The research was implemented in two cycles, involving 33 students, and utilized a mixed method of quantitative and qualitative approaches. Data were collected through classroom observations, pre-test, post-test, and students’ questionnaires. The results showed that students’ ability in speaking had greatly improved. After the first cycle, the average score rose from 48 on the pre-test to 73, and it further increased to 82 on the second cycle of the post-test. Moreover, in the final post-test, 91% of students received the minimum passing grade (≥ 75), up from 6% on the pre-test. The qualitative data supported these results, indicating increased student motivation, reduced anxiety, and enhanced self-assurance when speaking English. The findings suggest that the role-play method is effective in developing students’ speaking ability, motivation, and confidence in EFL classrooms.